Non-tuberculous mycobacteria lung disease due to Mycobacterium chimaera in a 67-year-old man treated with immune checkpoint inhibitors for lung adenocarcinoma: infection due to dysregulated immunity? - Azzarà, Cecilia; Lombardi, Andrea; Gramegna, Andrea; Ori, Margherita; Gori, Andrea; Blasi, Francesco; Bandera, Alessandra (BMC infectious diseases, 2023)
Immune checkpoint inhibitors (ICIs) are drugs growingly employed in cancer immunotherapy which have significantly improved the prognosis of several tumours. ICIs act by restoring the “exhausted” immune system and increasing the number of T cells active against pathogens losing tolerogenic signalling, which has been linked to an increased risk of infectious events. We present the case of a 67-year-old man with locally advanced lung adenocarcinoma treated with the anti-PD-L1 durvalumab. Three months after immunotherapy started, an apparent radiological progression was found with elements suggesting a parenchymal superinfection associated with weight loss, asthenia, and sputum emission. A bronchoalveolar lavage resulted positive for Mycobacterium chimaera , and treatment with amikacin iv (for eight weeks) and daily azithromycin, ethambutol, and rifampicin was started. Thirteen months after treatment started, the patient is alive with a stable lung condition. The case highlights the risk of non-tuberculous mycobacteria lung disease (NTM-LD) in patients receiving ICIs treatment. We hypothesise that durvalumab induced an exaggerated immune response toward the mycobacteria, leading to immunopathology and overt clinical manifestations. Clinicians should be aware of this possibility in patients receiving ICIs developing new signs/symptoms related to the respiratory tract, especially in countries with a high prevalence of NTM-LD.